2015
DOI: 10.1111/1346-8138.13082
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine porocarcinoma shares dermoscopic characteristics with eccrine poroma: A report of three cases and review of the published work

Abstract: Eccrine porocarcinoma (EPC) is a rare malignant skin tumor presumably arising from the intraepidermal ductal portion of the sweat gland. EPC occasionally mimics eccrine poroma (EP), seborrhea keratosis (SK), basal cell carcinoma (BCC), pyogenic granuloma (PG) and amelanotic melanoma with its clinical appearance as a pink nodule. Dermoscopy is an invaluable technique in diagnosing skin tumors. However, few cases of EPC have been reported using dermoscopic images, and their details were not well examined. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 11 publications
2
21
1
2
Order By: Relevance
“…The collarette sign has been reported in clear cell acanthoma, pyogenic granuloma, melanoma, basal cell carcinoma, angiokeratoma, Spitz naevus, eccrine poroma and rarely in Kaposi sarcoma . Zaballos and colleagues evaluated the dermoscopic findings of pyogenic granuloma, and in their study, the collarette sign was observed in three Kaposi sarcoma lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collarette sign has been reported in clear cell acanthoma, pyogenic granuloma, melanoma, basal cell carcinoma, angiokeratoma, Spitz naevus, eccrine poroma and rarely in Kaposi sarcoma . Zaballos and colleagues evaluated the dermoscopic findings of pyogenic granuloma, and in their study, the collarette sign was observed in three Kaposi sarcoma lesions.…”
Section: Discussionmentioning
confidence: 99%
“…2,16 The collarette sign has been reported in clear cell acanthoma, pyogenic granuloma, melanoma, basal cell carcinoma, angiokeratoma, Spitz naevus, eccrine poroma and rarely in Kaposi sarcoma. [17][18][19][20] Zaballos and colleagues 20 evaluated the dermoscopic findings of pyogenic granuloma, and in their study, the collarette sign was observed in three Kaposi sarcoma lesions. Histopathological correlation of the collarette sign in pyogenic granuloma was defined as hyperplastic adnexal epithelium that partially or completely surrounds the tumour.…”
Section: E52mentioning
confidence: 99%
“…Previously reported cases revealed the presence of polymorphous vascular pattern (hairpin, linear-irregular, dotted vessels), round-to-oval pink-white structureless areas and white-to-pink halo. [8][9][10] In the differential diagnosis, a wide spectrum of cutaneous pink tumours revealing polymorphous vascular pattern on dermoscopy should be considered, including eccrine poroma, amelanotic melanoma, non-melanoma skin cancer and pyogenic granuloma. 8 Wide surgical resection is currently the treatment of choice and should be accompanied by assessment for metastatic disease, as the presence of metastases was found in 31% of previously reported cases.…”
Section: Porocarcinoma Of the Nail: A Dermoscopic Observationmentioning
confidence: 99%
“…[8][9][10] In the differential diagnosis, a wide spectrum of cutaneous pink tumours revealing polymorphous vascular pattern on dermoscopy should be considered, including eccrine poroma, amelanotic melanoma, non-melanoma skin cancer and pyogenic granuloma. 8 Wide surgical resection is currently the treatment of choice and should be accompanied by assessment for metastatic disease, as the presence of metastases was found in 31% of previously reported cases. 1 Based on this case, it seems that nail porocarcinoma shares dermoscopic features of porocarcinoma at different anatomical locations.…”
Section: Porocarcinoma Of the Nail: A Dermoscopic Observationmentioning
confidence: 99%
“…1,5,8,9 Además se puede observar áreas sin estructura y cordones blanquecinos interconectados, siendo esto último altamente sugerente de poroma. 1 En la variante pigmetada se ha descrito la presencia de estructuras azul blanquecinas y globulillares inespecíficas y aperturas tipo comedón.…”
unclassified